Head impact in a snowboarding accident - Bailly, N.; Llari, M.; Donnadieu, T.; Masson, C.; Arnoux, P.-J. (Scandinavian Journal of Medicine & Science in Sports, 2017)
To effectively prevent sport traumatic brain injury (TBI), means of protection need to be designed and tested in relation to the reality of head impact. This study quantifies head impacts during a typical snowboarding accident to evaluate helmet standards. A snowboarder numerical model was proposed, validated against experimental data, and used to quantify the influence of accident conditions (speed, snow stiffness, morphology, and position) on head impacts (locations, velocities, and accelerations) and injury risk during snowboarding backward falls. Three hundred twenty-four scenarios were simulated: 70% presented a high risk of mild TBI (head peak acceleration >80 g) and 15% presented a high risk of severe TBI (head injury criterion >1000). Snow stiffness, speed, and snowboarder morphology were the main factors influencing head impact metrics. Mean normal head impact speed (28 ± 6 km/h) was higher than equivalent impact speed used in American standard helmet test (ASTM F2040), and mean tangential impact speed, not included in standard tests, was 13.8 (±7 km/h). In 97% of simulated impacts, the peak head acceleration was below 300 g, which is the pass/fail criteria used in standard tests. Results suggest that initial speed, impacted surface, and pass/fail criteria used in helmet standard performance tests do not fully reflect magnitude and variability of snowboarding backward-fall impacts.